Therapeutic and prognostic implications of immune-related adverse events in advanced non-small-cell lung cancer - Daniello, Lea; Elshiaty, Mariam; Bozorgmehr, Farastuk; Kuon, Jonas; Kazdal, Daniel; Schindler, Hannah; Shah, Rajiv; Volckmar, Anna-Lena; Lusky, Fabienne; Diekmann, Leonore; Liersch, Stephan; Faehling, Martin; et al. (Frontiers in oncology, 2021)
Introduction: PD-(L)1 inhibitors have improved prognosis of non-small-cell lung cancer (NSCLC), but can also cause immune-related adverse events (irAE) that complicate management. Methods: We analyzed NSCLC patients receiving PD-(L)1 inhibitors from 2012-2020 in a German academic center. Results: IrAE showed comparable frequencies in stage IV (198/894 or 22%) vs. III (14/45 or 31%, p=0.15), after anti-PD-(L)1 monotherapy vs. chemoimmunotherapy (139/483 vs. 58/213, p=0.75), and across treatment lines. In stage IV, irAE occurred after 3.1 months in median, affected multiple organs (median 2) in 27/894 patients, and were associated with PD-L1 positivity (25% vs. 14%, p=0.003), lower neutrophil-to-lymphocyte ratios (29% vs. 17%, p3 months), and average cumulative prednisone doses >700 mg for all organs, except for skin. Patients developing irAE had longer progression-free (PFS) and overall survival (OS) in multivariable 12/14-week landmark analyses including ECOG status, treatment line, treatment type, PD-L1 TPS, and NLR (median PFS 17 vs. 10 months, HR=0.68, p=0.009; median OS 37 vs. 15 months, HR=0.40, p<0.001), regardless of grade. OS was longest with skin (95% at 2 years) and shortest with pneumonitis, hepatitis, neurologic and cardiologic irAE (38%, 37%, 28%, and 0% at 2 years, p<0.001). Conclusions: Approximately one-fourth of immunotherapy-treated NSCLC patients develop irAE, most of which necessitate treatment suspension and steroids. Despite occurring more frequently with PD-L1 positive tumors, lower NLR, and better ECOG PS, irAE are independently associated with longer survival, especially when affecting the skin. Lethality is below 1%.
Gesehen am 05.08.2021